THE EFFECT OF SPORTS MASSAGE TOWARDS CORTISOL AND PRE-COMPETITION ANXIETY AMONG MALAYSIAN ELITE TENNIS ATHLETE - Pa, Wan Ahmad Munsif Wan; Salamuddin, Norlena; Zin, Noraziah Mohamad; Lian, Denise Koh Choon (The journal of contemporary issues in business and government, 2021)
Nowadays, psychological issues often occurs among elite athletes and were higher than the general population. However, this problem can be controlled by providing an appropriate intervention. In addition, studies on the impact of Sports Massage toward cortisol and pre-competition anxiety were still lacking in attention on tennis. Thus, this study was conducted to evaluate the effectiveness of Sports Massage intervention on cortisol and pre-competition anxiety. A total of 14 elite tennis athletes were participated in this study and were divided into treatment groups and control groups by using the Quasi-Experimental study design, quantitatively. Instruments used in this study were Enzyme-Linked Immunosorbent Assay (ELISA) and Competitive State Anxiety Inventory (CSAI-2). There were three phase of instrument measurement in this study namely pretest, first posttest and second posttest. Repeated Measures Two Way ANOVA was performed, there was a significant difference in the cognitive anxiety, somatic anxiety, and self-confidence (p < 0.05). However, there was no significant difference on cortisol (p > 0.05). These findings suggested as the basis for determining the effect of Sports Massage therapy towards cortisol level and pre-competition anxiety level among Malaysian elite tennis athlete.